A Reflection on Challenges Faced by Deaf Trainees in Effective Social Interaction in St. Angela Mumias Vocational School, Kakamega, Kenya - Brenda Mumbua Nzioka; Ong’ang’a H. M. Ouko; Isanda Backy (Randwick International of Social Science Journal, 2022)
The purpose of the study was to establish the challenges deaf trainees face in their social interactions. The study focused on St. Angela Mumias Vocational School for the Deaf, Kakamega County. The study was anchored on the Theory of Mind by David Premack (1978). A case study design was adopted. The study target was 103, including 95 deaf trainees, one principal, and 7 trainers. Purposive sampling technique was employed to select 3 trainers and the principal, while simple random sampling was used to select 39 deaf trainees. This study adopted a mixed-methods data collection approach. Questionnaires comprising both open-ended and close-ended questions were used to collect data from the principal and deaf trainees. In contrast, semi-structured interview schedules were used to collect primary data from trainers. Quantitative data was coded and analyzed using Statistical Package for Social Sciences (SPSS version 21). Descriptive data was represented in the form of mean, median, mode, correlation, frequency distribution tables, graphs, pie charts, and percentages. Qualitative data were coded systematically by hand, analyzed thematically and presented in narrative form. The findings revealed that only 27.8 % of deaf trainees interacted with the hearing trainees and they also do not share their problems and secrets. Based on the results, the study recommends that the government, through the Ministry of Education, decentralize sign language training to the villages and community settings to assist in enhancing communication between the Deaf and the hearing.